Penerapan Model Pembelajaran Jigsaw Dalam Meningkatkan Hasil Belajar Siswa Kelas X Pada Mata Pelajaran Sejarah Kebudayaan Islam Di MAN 2 Halmahera Utara - Aisa Ahmad; Darma Munawar (EDUKASI, 2023)
Learning is an effort to teach a person or group through various efforts and various strategies, methods and approaches towards achieving the planned goals. The purpose of this study was to find out the application of the Jigsaw learning model in improving class X student learning outcomes on the material on the development of the Prophet Muhammad's Da'wah in the Mecca period in the subject of SKI Madrasah Aliyah Negeri 2 Halmahera Utara. Research is a Class Action Research (CAR) to get the truth and practical benefits by taking action in a collaborative and participatory manner. The research subjects included 22 students of Class X IPA 1 at Madrasah Aliyah Negeri 2 North Halmahera, consisting of 13 girls and 9 boys. The results showed that the application of the jigsaw cooperative learning model could improve the learning outcomes of class X MAN 2 North Halmahera. In cycle I, the scores of students who had not reached the KKM were 7 students (31%), while in cycle II there was an increase in learning outcomes of 87.5% or 21 students who had completed. Student activity measured during learning in cycle I was still relatively low with an activity percentage of 31.81%, while in cycle II there was an increase of 95.45%. This means that the implementation of learning has been going very well.